French lyric diction workbook : a graded method of phonetic transcription which employs frequently occurring words from French art song literature - Montgomery, Cheri (S.T.M. Pub., 2006)
A graded method of phonetic transcription which employs frequently occurring words from French art song literature - includes practice exercises designed for in-class application of new material and individual student assignments.